QUALIMETRIC EVALUATION OF THE QUALITY OF COURSEWORK IN THE ACADEMIC DISCIPLINE "VOCATIONAL TRAINING METHODOLOGY" - Bachiieva , L. (Problems of Engineer-Pedagogical Education, 2022)
Among the priority areas in the development of the education system in Ukraine is the introduction of monitoring of quality of education. The accomplishment of this task is connected with the movement to the European education space, which requires constant improvement of the education system. One of the types of effective tools for monitoring is a factor-criterion model for evaluating a phenomenon or a process being studied. The paper presents a technology of organizing and conducting evaluation of the quality of coursework in the discipline "Vocational training methodology" using the developed factor-criterion model. Based on the sources of scientific information, the analysis of the concept "monitoring" has been carried out; its functions in the educational process have been identified. The academic discipline "Vocational training methodology" has proved to implement the methodological training of vocational education teachers, namely the formation of their competence to create didactic projects. The coursework is an individual didactic project, and its content, as well as the sequence of implementation stages, fully simulates the teacher’s activities. Thus, the coursework is one of the main components of training vocational education teachers and, accordingly, requires the development and implementation of objective tools for evaluating the results of the educational process on the basis of qualimetry. There have been shaped and carried out actions to create a factor-criterion model, namely: definition of the essence of the term "factor-criterion model for measuring the quality of coursework"; substantiation of the components of the model for evaluating the quality of coursework; determination of factors and criteria for measuring the quality of coursework; description of the method for determining the weighting coefficients of each of the factors and criteria; building a model for measuring the quality of coursework. The following factors have been identified: content quality of execution; quality of presentation; quality of the speech delivery with a fragment of the developed didactic project on the topic, – the criteria are the content of each component. Based on the results of the experimental study, the developed tools have proved to be effective because of their contribution to the positive dynamics of the quality of education. The developed technology can be used in higher education institutions with the aim of preparing for the development of factorcriteria models for evaluating students’ coursework.